PENGELOLAAN ARSIP KEPEGAWAIAN DI KANTOR REGIONAL I BADAN KEPEGAWAIAN NEGARA YOGYAKARTA - , PUSPITA DWI; , Taufik Hery Purwanto, S.Si, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The increasing number of people are increasingly rising in the District of Gondomanan cause people will trade needs to meet the increasing needs of the economy. In addition, the accessibility factor and good utility, located in the District Gondomanan also Encourage economic activity of the area, so we need an appropriate location and strategic. Trade research aims to Determine how the data acquisition using Quickbird imagery to Determine appropriate land for trade and location mapped the location of priority trade in the District of Gondomanan using GIS. The method used in the prioritization of trade location is tiered or quantitative methods (scoring) of the influencing parameters include land use, accessibility of positive, negative accessibility, land price, population density, and educational facilities. The larger the value, the greater the dignity of influence to make trade a priority area. Another method used is the process of merging overlay maps parameters to produce a map of priority areas of trade. Utilization of remote sensing image generating parameters such as land use, accessibility of positive, negative accessibility, land price, population density, and distance to the field of education facilities. Application of Geographic Information Systems as a trade area analysis technique parameters assist in data entry, data processing, analysis and results in the form of a map of priority trade areas. The final results obtained from this study is the Priority Map Trade Zone District of Gondomanan Scale 1:10,000, where on the map the location presents three priority classes of trade which consists of high priority, medium, and low.